Gender Role Appraisal in Rice Farming of Coastal Agro Eco-Systems in Eastern India (Indian Journal of Extension Education, 2013)
The study was based on the gender perspectives in rice farming in one of the most intensive rice producing area of Eastern India, i.e. Balasore district of Odisha state. Information was collected from 240 randomly selected small and marginal farm women through a well structured interview schedule during 2011. Difference in role perception of farm women and their counterparts in rice farming was analysed. The significant difference in perception about various operations found among the farm women and their husbands was proved to have an impact upon their participation in rice farming. Among the independent variable education, was negatively correlated with the participation of farm women in rice farming while economic and social orientation of farm women were found having a positive significant correlation. Further 82.44 per cent of the combined contribution of all the independent variables was found significant in predicting the participation of farm women in rice farming. Therefore, it is recommended that socio-economic orientation of farm women must be improved in rice farming in order to get rid of discrimination against the farm women.